Influence of competence and locus of control on readiness of accounting department students facing the world of work era industrial revolution 4.0 - Saraswati, Anak Agung Sagung Dea; Putri, I Gusti Ayu Made Asri Dwija; Suprasto, Herkules Bambang; Sari, Maria Mediatrix Ratna (International research journal of management, IT and social sciences, 2020)
This study discusses ethical competencies, knowledge competencies, capability competencies, relationship competencies, analytical competencies, and locus of control on the readiness of students majoring in accounting in the world of work of the revolution era 4.0. The population of the study was in the 2017 class of faculty of economics and business students of Udayana University. The research sample was determined by the nonprobability sampling method which obtained a total sample of 166 people. The data analysis technique used is multiple linear regression analysis. The results showed that the results showed ethical competence, knowledge competence, capability competence, relationship competence, analytical competence, and locus of control had a positive effect on the readiness of students majoring in accounting in connecting the world of work of the industrial revolution era 4.0.